Fluorides - Liteplo, R; Howe, P; Malcolm, Heath (WHO, 2002)
This book evaluates the risk to human health and the environment posed by exposures to fluorides. It is widely known that fluoride has both positive and negative effects on human health, and there is a narrow range between intakes that are associated with these effects. Cases of skeletal fluorosis associated with the consumption of drinking water containing elevated levels of fluoride are reported.Fluoride is ubiquitous in the environment and virtually all foodstuffs contain at least trace amounts of fluoride. The amount of fluoride present naturally in non-fluoridated drinking water is highly variable, being dependent upon the individual geological environment. Also, fluorides, especially hydrogen fluoride, are important industrial compounds and they are used in aluminum production, glass manufacturing and so on.This document focuses on environmental exposure to fluoride derived mostly from inorganic sources and its effects on humans, animals and other biota. Data on hydrogen fluoride, calcium fluoride, sodium fluoride, sulfur hexafluoride and silicofluorides are covered, as these compounds are considered to be the most relevant of the inorganic fluorides on the basis of quantities released to the environment, environmental concentrations and toxicological effects on living organisms. A review of studies on the environmental fate and concentration of fluorides is also presented in this document.
Environmental health criteria, ISSN 0250-863X 227
Keywords: environmentální zdraví; fluoridy; Environmental Exposure; pracovní expozice; environmentální vědy; hodnocení rizik; Risk Assessment; veřejné zdravotnictví; Occupational Exposure; Fluorides; Environmental Health; vystavení vlivu životního prostředí